Estimation of the structure of the mixed forest stands of Stryisko-Syanska Verkhovyna using gis technologies - Korol, M.; Havryliuk, S.; Tokar, O.; Vovk, O.; Kolyasa, L. (Видавництво Львівської політехніки, 2018)
The spatial structure of the old-growth mixed forest stands of Stryisko-Syanska Verkhovyna was studied using state-of-the-art approaches and GIS technologies. Thematic maps of the spatial structure of the forest plantations were developed.
Keywords: forest stands; spatial structure of stands; GIS technology; thematic map; 630*524.4; 004.942